Potential risk factors associated with seropositivity for Toxoplasma gondii among pregnant women and HIV infected individuals in Ethiopia: A systematic review and meta-analysis. - Zewdu Seyoum Tarekegn; Haileyesus Dejene; Agerie Addisu; Shimelis Dagnachew (Public Library of Science (PLoS), 2020)
Background Toxoplasma gondii is an obligate intracellular and neurotropic apicomplexan protozoan parasite infecting almost all warm-blooded vertebrates including humans. To date in Ethiopia, no systematic study has been investigated on the overall effects of potential risk factors associated with seropositivity for Toxoplasma gondii among pregnant women and HIV infected individuals. We intended to determine the potential risk factors (PRFs) associated with seropositivity for Toxoplasma gondii from published data among pregnant women and HIV infected individuals of Ethiopia. Methodology An systematic review of the previous reports was made. We searched PubMed, Science Direct, African Journals Online, and Google Scholar for studies with no restriction on the year of publication. All references were screened independently in duplicate and were included if they presented data on at least two risk factors. Meta-analysis using the random or fixed-effects model was made to calculate the overall effects for each exposure. Results Of the 216 records identified, twenty-four reports met our eligibility criteria, with a total of 6003 individuals (4356 pregnant women and 1647 HIV infected individuals). The pooled prevalences of anti-Toxoplasma gondii antibodies were found at 72.5% (95% CI: 58.7% - 83.1%) in pregnant women and 85.7% (95% CI: 76.3% - 91.8%) in HIV infected individuals. A significant overall effect of anti-Toxoplasma gondii seropositivity among pregnant women (p < 0.05) was witnessed with age, abortion history, contact with cats, cat ownership, having knowledge about toxoplasmosis, being a housewife and having unsafe water source. Age, cat ownership, and raw meat consumption were also shown a significant effect (p < 0.05) to anti-Toxoplasma gondii seropositivity among HIV infected individuals. Conclusions This review showed gaps and drawbacks in the earlier studies that are useful to keep in mind to design accurate investigations in the future. The pooled prevalence of anti-Toxoplasma gondii antibodies was found to be higher among pregnant women and HIV infected individuals. This suggests that thousands of immunocompromised individuals (pregnant women and HIV infected patients) are at risk of toxoplasmosis due to the sociocultural and living standards of the communities of Ethiopia. Appropriate preventive measures are needed to reduce the exposure to Toxoplasma gondii infection. Further studies to investigate important risk factors are recommended to support the development of more cost-effective preventive strategies.